The State and Dilemma of Post-Colonial Nigeria: An Explanatory Perspective of Security Governance Failure - Obikaeze, Victor C.; Udoh, Ogbonnaya N.; Adebogun, Olayinka B.; Enapeh, Oluchi (ABUAD Journal of Social and Management Sciences, 2023)
The post-colonial Nigerian state has experienced series of internal political altercations due to the consistent and persistent behavioural patterns of the political elites, whose inordinate political ambitions have often revolved around appropriating state apparatuses as well as primordial forces for their personal aggrandisement, against the majoritarian vital primary interest of the downtrodden. To this effect, governance has suffered over the years in the hands of the recycled dominant political class that has produced and manipulated institutions of government, thereby deepening copiously and rapaciously spatial social and economic inequalities between the elite and masses. In view of this circumstance, the study is aimed at x-raying the explanatory contradictions responsible for security governance failure in Nigeria after decades of political independence. The study adopted qualitative-descriptive method and relied on secondary sources of data collection. The ‘‘theory of post-colonial state’’ is employed as the main underpinning analytical construct that scientifically studies the society as a whole, and takes into consideration the convergence of ‘unity of the opposites’.